Determination of alpha- and beta-asarone in traditional products containing Acorus calamus rhizome by gas chromatography mass spectrometry / Amirul Mohd Mahfuz Mannan - Amirul Mohd Mahfuz, Mannan (2017)
The study was conducted to develop an analytical method to identify and quantify alpha- and beta-asarone from traditional products that contain Acorus calamus rhizome. Alpha- and beta-asarone are the major active compounds in rhizome of Acorus calamus which are responsible for the plants’ therapeutic effects such as relieving stomach cramps, dysentery, asthma, antimicrobial, anthelmintic, insecticides, tonic and stimulants. However, there were reports of mammalian toxicity and carcinogenicity of asarones that discourage the medicinal use of this plant. International regulatory authorities have set different restrictions for Acorus calamus as some countries have complete prohibition of its use while other countries enforce content limitation. Alpha- and beta-asarone were extracted from traditional products by sonication method using methanol as solvent. Gas chromatography mass spectrometry was chosen for the determination of alpha- and beta-asarone because the analysis is reliable, cost effective and rapid. Standards of alpha- and beta-asarone have shown distinct separation and elute at about six minutes with this method. Mass spectra of alpha- and beta-asarone were obtained after running scan mode and these mass spectra were selected in Selected Ionizing Monitor (SIM) mode for quantitation purposes. Nine samples in different dosage form (three capsulated powder, one tablet and five oils) have been collected from current market for screening of alpha- and beta-asarone. Only one sample of capsulated powder form was found to contain beta-asarone. Alpha- and beta-asarone were not detected in the oil form products. Negative results for alpha- and beta-asarone might be due to the heterogeneous nature of herbal substances in traditional product and lack of efficiency of the extraction method. Overall, the developed method is appropriate to quantify the level of alpha- and beta-asarone in traditional products containing Acorus calamus rhizome.